Implementation of Digital-Based Performance Management in Improving the Quality of Educational Administration Services and Educational Personel - Ningsih, Syafitri; Ismaya, Bambang; Wahyudin, Undang Ruslan (Research Horizon, 2025)
In the digital era, schools are increasingly required to modernize administrative processes to meet the demands of efficiency and quality service. This study aims to examine the implementation of digital performance management to improve educational administration and staff performance. Using a qualitative case study approach, data were collected through in-depth interviews, participant observations, and document analysis, then analyzed following Miles’ interactive model of data condensation, display, and conclusion drawing. The findings show that digital performance management has improved administrative workflows by shifting from manual to real-time, structured, and paperless processes, resulting in more efficient, accurate, and transparent services. Service quality improved across speed, reliability, responsiveness, and accountability. Challenges remain, including variations in staff digital competence, dependence on ICT infrastructure, and occasional network instability. Recommended strategies include ongoing staff training, technological infrastructure enhancement, periodic system evaluation, and strong digital leadership. Digital performance management plays a strategic role in enhancing school administration quality and provides valuable insights for the digital transformation of educational administration. These findings are expected to contribute to policy development on the digitalization of secondary school educational administration.